The Energy of Break or Deformation in Some Semi- Crystalline Polymers - H. Jassim, Widad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of the current study is the investigation of tensile behavior of the semi - crystalline polymers : polypropylene (PP ) , high density polyethylene(HDPE) and low density polyethylene (LDPE) . The energy to break or deformation was determined as a function of extension rates , ( PP) was break at extension rate (5) mm/min but (HDPE) break at higher extension rates (25) mm/min while( LDPE) not break even at very high extension rates but it is deformation or failure .